(untitled) (International Journal of Management and Sustainability, 2024)
This research aims to investigate the factors influencing talent retention within Malaysia’s IT services sector. Specifically, it seeks to determine the impact of reward programs, career development, and work-life balance on talent retention. Conducted in a descriptive, non-contrived setting, this study employs a convenience sampling method. Self-administered online questionnaires are utilized for quantitative data collection. The research employs a correlation method to examine the association between reward programs, career development, work-life balance, and talent retention. Questionnaires, adapted from prior research, are distributed via WhatsApp and email, targeting a minimum sample size of 384. Data analysis is conducted using SPSS, a software suite designed for social science research. The study reveals that two out of the three hypotheses establish a significant relationship between rewards programs, career development, work-life balance, and the retention of talented workers in Malaysia’s IT services sector. These findings suggest that attention to rewards programs and career development significantly influences talent retention in the Malaysian IT industry. The study recommends further exploration of variables that might exert a more substantial impact on talent retention within the Malaysian IT services sector. This research contributes valuable insights into the critical determinants of talent retention in Malaysia’s IT services sector. The identified relationships between rewards programs, career development, and work-life balance offer practical guidance for industry professionals, informing strategies to enhance talent retention practices.